Math, asked by devyu46051, 1 year ago

Prove than tan inverse 1 by 2 + tan inverse 1 by 5 + tan inverse 1 by 8 = pi by 4

Answers

Answered by rishu6845
2

\underline{\bold{To \: prove}}\longrightarrow \\  {tan}^{ - 1}  \dfrac{1}{2}  +  {tan}^{ - 1}  \dfrac{1}{5}  +  {tan}^{ - 1}  \dfrac{1}{8}  =  \dfrac{\pi}{4}

\underline{\bold{Concept \: used}}\longrightarrow \\ \boxed{ {tan}^{1} x +  {tan}^{ - 1} y =  {tan}^{ - 1}  \dfrac{x + y}{1 - xy}}

\underline{\bold{Solution}}\longrightarrow \\ LHS= {tan}^{  - 1}  \dfrac{1}{2}  +  {tan}^{ - 1}  \dfrac{1}{5}  +  {tan}^{ - 1}  \dfrac{1}{8}

 = ( {tan}^{ - 1}  \dfrac{1}{2}  +  {tan}^{ - 1}  \dfrac{1}{5} ) +  {tan}^{ - 1}  \dfrac{1}{8}

 =  {tan}^{ - 1}  \dfrac{ \dfrac{1}{2}  +  \dfrac{1}{5} }{1 -  \dfrac{1}{2}  \times \dfrac{1}{5}  }  \:  \:  +  {tan}^{ - 1}  \dfrac{1}{8}

 =  {tan}^{ - 1}  \dfrac{ \dfrac{5 + 2}{10} }{ \dfrac{10 - 1}{10} }  +  {tan}^{ - 1}  \dfrac{1}{8}

 =  {tan}^{ - 1}  \dfrac{7}{9}  +  {tan}^{ - 1}  \dfrac{1}{8}

 =  {tan}^{ - 1}  \dfrac{ \dfrac{7}{9}  +  \dfrac{1}{8} }{1 -  \dfrac{7}{9} \times  \dfrac{1}{8}  }

 =  {tan}^{ - 1}  \dfrac{ \dfrac{56 + 9}{72} }{ \dfrac{72 - 7}{72} }

 =  {tan}^{ - 1}  \dfrac{65}{65}

 {tan}^{ - 1} (1)

 =  {tan}^{ - 1} (tan \dfrac{\pi}{4} )

 =  \dfrac{\pi}{4} =RHS

Similar questions